Fatigue Behaviour of Nodular Cast Iron at Various Loading Cycle Asymmetry - Vechet, Stanislav; Kohout, Jan; Hanzlikova, Klara; Hruby, Vojtech (Communications - Scientific letters of the University of Zilina, 2006)
Fatigue behaviour of nodular cast irons is described in specialized literature quite well but the majority of fatigue tests in high cycle region has been made at symmetrical bending or at symmetrical tension-compression loading. The role of loading cycle asymmetry is very important because the fatigue limit of nodular cast irons is substantially influenced by mean static stress. Unfortunately, the number of papers describing the influence of mean static stress is quite low. The aim of the presented paper consists in presenting the results of long-term research of nodular cast irons at high cycle region at different loading cycle asymmetry. Several heats with various heat treatments leading to various structures of matrix were used for fatigue tests performed mainly at symmetrical tension-compression loading and at repeating tensile loading. From S–N curves the fatigue limits for 107 cycles were determined and then used for the calculation and construction of the Haigh and the Smith diagrams. Nodular cast irons seem to be more sensitive to mean static stress than structural steels. It was found that, in contrast to many papers, the dependence of upper stress on mean stress is not linear but parabolic with the exponent lower than 1 whose value is linear function of UTS.